Overlap in Family Conversations on the “Not Enough Nelson” YouTube Channel: A Conversation Analysis Approach - Sarah Mudrika Zain; Lili Awaludin; Ika Yatmikasari (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
This study examines the types of overlap and their functions in fostering closeness and engagement among family members, as observed on the YouTube channel “Not Enough Nelson,” with the aim of identifying the phenomenon of overlap in everyday conversation. Theoretically, this study contributes to the development of Sack et al.’s Conversation Analysis theory in the context of social media by applying (Jefferson, 1984) theory. In line with the proliferation of daily activities shared via social media, this study employs a qualitative analysis approach from (Cresswell, 2009) to analyze 3 videos transcribed by selecting relevant comments that reflect the phenomenon of overlap in conversation. The findings of this study indicate that continuing overlap occurs most frequently with 13 instances, followed by terminal overlap with 5 instances, choral overlap with 5 instances, and conditional access overlap with 1 instance as the least frequently occurring overlap phenomenon.